Multi-criteria decision making for the selection of a production control policy. (2nd September 2010) - Sharma, Sanjay; Agrawal, Narayan
The present article deals with the single product, serial manufacturing system with ten production stages in tandem. Various performance criteria such as fill rate, WIP, throughput, etc. have been included with production cost. Analysis has been made with the use of Poisson demand for a manufacturing line and a soft experimental model has been proposed. Some of just-in-time techniques have been compared in the discussed environment. Methodology of analytic hierarchy process with the mathematical framework underlying the eigenvector method has been described for the purpose of comparison and the optimal selection. Change in weight of parameters affects the final rankings of alternatives which is also included in this study through sensitivity analysis.